The relationship between principal leadership skills, organizational citizenship behaviour and intellectual capital in secondary schools in Pakistan / Muhammad Niqab - Muhammad, Niqab (2015)
The purpose of this study is to identify and analyse whether principal leadership skills (PLS) affect intellectual capital (IC) of secondary school directly or through the mediation of organizational citizenship behaviour (OCB) of teachers. This is basically a co-relational study, with the main focus revolving around the relationships among the PLS, IC, and OCB in secondary schools in Pakistan. This quantitative study was conducted using a survey instrument comprising 61 items representing PLS, OCB, and IC. Questionnaires were distributed to 465 teachers of secondary schools situated in Khyber Pakhtunkhwa Province and affiliated with Federal Board of Intermediate and Secondary Education (FBISE), Islamabad, Pakistan. A total of 408 teachers returned the survey instrument in complete form. Data were analysed with the help of statistical tools, SPSS version 22, and AMOS graphics version 22. Demography of the respondents is such that 177 male (43%) and 231 female (57%) teachers took part in this study. They have different age, professional qualification, and majority of them (61%) possess notable experience. Majority (78%) of the teachers also possess academic qualification of master’s degree. Data obtained was found to be normally distributed. Results of the contemporary study show that principals working in these secondary schools possess leadership skills, although the level of these skills is different in different organizations depending upon their structural capital (Norms, service structure, infra-structure, planning and implementation procedures and training opportunities) and type of school. OCB is quite helpful in enhancing IC of the schools. Correlation among variables and its dimensions provides important information, that PLS especially the behavioural skills are required to boost OCB and IC. Correlation between OCB and IC is higher in all three types of schools. The proposed theoretical model is the firm integration of the three fields: principal leadership skills (educational leadership), OCB (organizational management) and IC (business education/human iv economics). This could be an interesting contribution to the literature. This study provides a roadmap for improvement in education system of Pakistan. Therefore more time and investment is being suggested for the development of intangible assets (intellectual capital) rather than the tangible assets (physical assets) to get a competitive advantage as this dynamic capability approach should bring more development in terms of the intellectual capital of the secondary school which in turn will improve student’s outcome because teachers have a direct relation with student’s outcome, the ultimate goal of a school.